The Influence of Fashion Trends, Store Atmosphere, and Consumer Preferences on Buying Interest - Putri Ramadani; Kartika Sari Lubis (Husnayain Business Review, 2025)
Consumer buying interest is a behavior that reflects an individual's desire to buy or choose a product based on the experience of use and the drive to own the product. This study aims to analyze the influence of Fashion Trends, Store Atmosphere, and Consumer Preferences on Consumer Buying Interest in Bata Shoes in MMTC Branches. The type of research used is causal associative with a quantitative approach. The research population consists of consumers who have visited or are visiting MMTC Bata, with non-probability sampling techniques through accidental sampling. The number of samples was determined using the Lameshow formula for 96 respondents, then rounded up to 150 respondents to avoid bias. The results of the study showed that Fashion Trends and Store Atmosphere partially had a positive and significant effect on Consumer Buying Interest, while Consumer Preferences did not have a positive and significant effect. Simultaneously, these three variables have a positive and significant effect on Consumer Buying Interest. The Adjusted R Square value of 0.124 indicates that 12.4% of Consumer Buying Interest can be explained by Fashion Trends, Store Atmosphere, and Consumer Preferences, while the remaining 87.6% is influenced by other factors outside of this study.